O controle fiscal eletrônico da produção de bebidas: uma análise setorial sob a perspectiva do desempenho da arrecadação do ICMS do estado do Ceará no período de 2002 a 2011 - Pinheiro, Luiz Fernando (2015)
The aim of this study was to investigate the effect of electronic fiscal control of the production of beverage composed by the Flow Measurement System - SMV and the Liquor Control System – Sicobe, on the level of the collection of ICMS, of beers and soft drinks manufactured at the state of Ceará. We used the the database of beverage factories of the state of Ceará in the period of 2002 to 2011 on following parameters, the monthly collection of ICMS, the amount of collect tax over industrialized products – IPI, the number of jobs and the amount of electricity consumption. The industries were classified into two categories of taxpayers: the hot beverage and cold beverages industries. We used the methodology difference of difference, commonly applied to natural experiments.